Diverse real-life outcomes after intensive risk-adapted therapy for 1034 AML patients from the CETLAM Group - Guadalupe Oñate; Ana Garrido; Montserrat Arnan; Helena Pomares; Ester Alonso; Mar Tormo; Marina Diaz-Beya; Susana Vives; Lurdes Zamora; Antonia Sampol; Rosa Coll; Olga Salamero; et al. (Blood Cancer Journal)
Abstract Given the heterogeneity of acute myeloid leukemia patients, it is necessary to identify patients considered fit for intensive therapy but who will perform poorly, and in whom alternative approaches deserve investigation. We analyzed 1034 fit adults ≤70 years intensively treated between 2012 and 2022 in the CETLAM group. Young adults ( ≤ 60 years) presented higher remission rates and improved survival than older adults above that age (CR 79% vs. 73%; p = 0.03 and 4-yr OS 53% vs. 33%; p < 0.001). Remission and survival outcomes varied among different genetic subsets. An especially adverse genetic group included complex, monosomal karyotype, TP53 alterations (deleted/mutated), and MECOMr. Transplant feasibility in this very adverse risk group was low, and OS and EFS at 4 years were 14% and 12%, in contrast to 70% and 57% in the favorable group and 38% and 32% in all other patients. We integrated clinical and genetic data into the Intensive Chemotherapy Score for AML (ICSA) with 6-risk categories with significantly different remission rates and OS, validated in another cohort of 581 AML patients from a previous CETLAM protocol. In summary, we identified groups of fit patients that benefit differently from an intensive approach which may be helpful in future treatment decisions.